2009
DOI: 10.1249/jsr.0b013e31819d6b7b
|View full text |Cite
|
Sign up to set email alerts
|

Lower Gastrointestinal Distress in Endurance Athletes

Abstract: Training regimens and race days place significant demands upon both the competitive endurance athlete and the frequent-recreational runner. Lower gastrointestinal derangements, especially those involving diarrhea and rectal bleeding, are common and can impact adversely both the performance and the health of the athlete. While most cases are relatively benign, more significant and severe symptoms may not only impair sports performance, but also signify more serious disease. The sports medicine clinician should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…It was observed that forced treadmill exercise exacerbated inflammation, while voluntary exercise was protective in experimental colitis [15]. It is interesting that intensive exercise in humans, such as long-distance running, could lead to ‘runner’s ischaemic colitis’ involving bloody diarrhoea, fatigue and fever [16]. …”
Section: Introductionmentioning
confidence: 99%
“…It was observed that forced treadmill exercise exacerbated inflammation, while voluntary exercise was protective in experimental colitis [15]. It is interesting that intensive exercise in humans, such as long-distance running, could lead to ‘runner’s ischaemic colitis’ involving bloody diarrhoea, fatigue and fever [16]. …”
Section: Introductionmentioning
confidence: 99%
“…It is known that intensive exercise such as long distance running and triathlons could cause nausea, heartburn, diarrhea, or even gastrointestinal bleeding and marathon runners suffer from “runner's ischemic colitis,” involving bloody diarrhea, fatigue, and fever [20]. The involvement of physical activity in prevention of colon cancer [21] has been well proven, but the effect of physical activity on IBD is less documented and the importance of exercise as adjunct anti-inflammatory therapy has been suggested [2224].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise-induced GI symptoms seem to be caused predominantly by increased sympathetic nervous system activity that redistributes blood flow during exercise from the splanchnic organs to the working skeletal muscles, heart, lung and brain 1 14. This often leads to GI ischaemia, which may result in GI symptoms 1 15.…”
Section: Introductionmentioning
confidence: 99%